Conical multiple-layered Pt deposits on Au and its adsorption stoichiometries of CO and hydrogen. (10th November 2018) - Lee, Jaesung; Yoo, Jae Kwang; Kim, Jandee; Sohn, Youngku; Rhee, Choong Kyun
Abstract: This work demonstrated a method, termed iodine route, to produce height-controllable Pt deposits on Au using irreversible adsorption. Characterization of Pt deposits was performed utilizing scanning tunneling microscopy (STM), X-ray photoelectron spectroscopy and cyclic voltammetry. The iodine route sequentially utilized iodine adsorption, selective replacement of adsorbed iodine on Pt deposits with CO, and removal of adsorbed CO to produce adsorbate-free Pt deposit surfaces on iodine-covered Au surface. Execution of additional Pt deposition on the particular surface permitted selective growth of Pt on the existing Pt deposits to produce conical tall multiple-layered Pt deposits of height of 4–6 atomic layers without rim of single-layered Pt-Au alloy. A comparison of Pt deposits formed via iodine route with those produced via CO and conventional routes revealed that their physical and chemical properties depended on deposition route. Pt deposits of conventional route were double-layered plateau with wide rims of single-layered Pt-Au alloy, while CO route yielded single-layered Pt-Au alloyed deposits. The adsorption stoichiometries of CO and hydrogen on Pt deposits were evaluated using electrochemical coverages of the adsorbates and STM coverage of surface Pt. A strong correlation between adsorption stoichiometric values and physical shapes of Pt deposits was revealed. Adsorption of CO and hydrogen on single-layered Pt-Au alloy enhanced so that the adsorption stoichiometries were verified to be ∼2, ascribable to adsorption on Au atoms in the Pt-Au alloy. On multiple-layered Pt deposits the adsorption stoichiometry of CO was similar to that on polycrystalline Pt, while that of hydrogen was ∼0.5. The observation was discussed in terms of mutual interactions between Pt and Au and crystallographic effect of highly stepped surfaces of conical tall multiple-layered Pt deposits. Graphical abstract: